Características sensoriais, físico-químicas e atividade biológica da própolis produzida no semiárido do estado do Rio Grande do Norte, Brasil - Ferreira, Joselena Mendonça (Universidade Federal Rural do Semi-Árido, 2015)
Surveys of propolis have shown how this product has the potential for various therapeutic purposes. However, it has been found that this resin has a variability of compounds and biological activities depending on their place of origin, due to differences in vegetation from one location to another. The objective of this study was to verify the organoleptic, physico-chemical, and antimicrobial and antioxidant activity of propolis produced in different cities in the state of Rio Grande do Norte (Mossoró, Areia Branca, Alto do Rodrigues, Afonso Bezerra and Cerro Cora). Was identified the months of highest production in the apiaries of Mossoró and Alto do Rodrigues and variations in their properties to be assessed in two different periods of the year (post- rainy and dry). The propolis samples were collected in the five apiaries, each with 9 beehives of Langstroth type containing colonies of Apis mellifera bees. The method of production occurred after the introduction of a wooden bar with dimensions of 370 x 20 x 20 mm in the front and one at the rear, between the nest and the supers, creating a space of approximately 20 mm on each side where propolis produced was collected. After harvesting, the propolis samples were weighed, evaluated when the organoleptic characteristics (color and consistency) and stored in a freezer. For extraction in ethanol, were made set of propolis samples collected from colonies per apiary, 4 for sample Mossoró, 2 of Alto do Rodrigues, one of Areia Branca and 1 Afonso Bezerra and 1 Cerro Cora, totaling 9 sets sample. Thereupon, ethanolic extracts were made to quantify these phenols, flavonoids, total waxes, antimicrobial and antioxidant activities. For the antioxidant, free radical DPPH tests were performed and β-carotene system / linoleic acid. In the evaluation of the antimicrobial activity, the extracts were tested on the bacteria Staphylococcus aureus and Escherichia coli. Propolis of the county Alto do Rodrigues had the highest means of production compared to the apiary in Mossoró. The extracts showed significant results in all tests, with makeup and diverse biological activity. Seven of the nine samples analyzed possessed levels of waxes according to the required by law. There was a significant correlation between the levels of waxes and total phenolic content (R2> 0.5). Samples of propolis Afonso Bezerra and Mossoro had higher levels of flavonoids commonly found in the Brazilian propolis samples. The High extracts of Rodrigues, Afonso Bezerra and Mossoro were more promising in physical chemistry evaluation and antioxidant and antimicrobial activity. The antioxidant activity of the sample Alto do Rodrigues (52%) along with the sample Areia Branca (75%) had the highest percentage by methods DPPH system and β-carotene / Linoleic acid, respectively. The antimicrobial activity tests to S. aureus and E. coli, samples of Alto do Rodrigues and Afonso Bezerra performed better in antimicrobial activity, for having formed halos of inhibition at all concentrations tested in both the strains. In general, the samples had diverse biological activity and physical-chemical profile
Sensory characteristics, physico-chemical and biological activity of propolis produced in the semiarid region of the state of Rio Grande do Norte, Brazil
Keywords: Bee; Propolis; antioxidant; Organoleptic characteristics; Antimicrobial; Abelha; Própolis; Antioxidante; Características organolépticas; Antimicrobiana; CIENCIAS AGRARIAS::MEDICINA VETERINARIA